Current and future direct healthcare cost burden of chronic obstructive pulmonary disease in Alberta, Canada. Issue 1 (2nd January 2020) - Tran, Dat T.; Thanh, Nguyen Xuan; Ohinmaa, Arto; Mayers, Irvin; Jacobs, Phillip
Abstract: OBJECTIVES: To examine the resource use and healthcare costs for chronic obstructive pulmonary disease (COPD) in Alberta, Canada between 2008 and 2016 and model the future costs to 2030. METHODS: Interlinked hospitalization, ambulatory care, practitioner claims and drug databases in Alberta were used to identify COPD healthcare encounters and medications. Canadian Institution for Health Information Cost of a Standard Hospital Stay was used to calculate hospitalization and ambulatory costs and Alberta Drug Benefit List was used to provide drug unit costs. Linear regression and generalized linear model were used to project future COPD healthcare costs. RESULTS: The study included 68, 812 hospitalizations, 159, 750 ambulatory care visits, 1, 239, 801 practitioner claims and 3, 103, 408 drug dispensing events of 70, 585 unique patients with COPD. The prevalence of health services use decreased (2008: 1, 831 per 100, 000 population; 2016: 1, 683; p < 0.001), while the patient age increased over time (mean age, 2008: 67.6 years; 2016: 69.9 years; p < 0.001). Number of hospitalizations increased but hospital length of stay decreased over time. A hospitalization with COPD costs CAN12, 994 while an ambulatory care visit costs CAN602. Annual healthcare costs increased from CAN115.5 in 2008 to CAN170.5 million in 2016 ( p < 0.001). Hospitalization and drug costs accounted for 65.5% and 19.7%, respectively. Annual healthcare costs for COPD were projected to reach CAN412.5 million in 2030. CONCLUSION: The healthcare cost burden of COPD for health systems is substantial and is projected to increase further. Interventions to shift COPD management from inpatient to less costly outpatient and home settings to alleviate the cost burden are needed.